Tuesday

February 9, 2016
Total # Posts: 2,045

**Math**

Note that, in this sequence, each term is twice the previous term. 6 / 4 = 2 * 3 / 4 12 / 4 = 2 * 6 / 4 = 3 24 / 4 = 2 * 12 / 4 = 2 * 3 = 6 48 / 4 = 2 * 24 / 4 = 2 * 6 = 12 96 / 4 = 2 * 48 / 4 = 2 * 12 = 24 192 / 4 = 2 * 96 / 4 = 2 * 24 = 48 384 / 4 = 2 * 192 / 4 = 2 * 48 = 96...
*March 23, 2015*

**Trigonometry**

943 ° = 720 ° + 223 ° = 2 * 360 ° + 223 ° Coterminal angle = 223 °
*March 19, 2015*

**Math Help Please!!!**

- 10 x + y = 4 x = - 2 - 10 * ( - 2 ) + y = 4 20 + y = 4 y = 4 - 20 = - 16 x = - 1 - 10 * ( - 1 ) + y = 4 10 + y = 4 y = 4 - 10 = - 6 x = 0 - 10 * 0 + y = 4 0 + y = 4 y = 4 x = 1 - 10 * 1 + y = 4 - 10 + y = 4 y = 4 + 10 = 14 x = 2 - 10 * 2 + y = 4 - 20 + y = 4 y = 4 + 20 = 24
*March 19, 2015*

**Math**

an = a1 + ( n - 1 ) d a10 = 3 + ( 10 - 1 ) * 6 a10 = 3 + 9 * 6 = 3 + 54 = 57
*March 14, 2015*

**Math**

In arithmetic sequence : an = a1 + ( n - 1 ) d Where: a1 is the first term of the sequence d is the common difference n is the number of the term a1 = 3 a4 = 3 + ( 3 - 1 ) d = 3 + 2 d a13 = 3 + ( 13 - 1 ) d = 3 + 12 d 1st, 4th, and 13th term forming a geometric sequence, so : ...
*March 14, 2015*

**Math**

2 / 3 = 2 / 3 * 1 = ( 2 / 3 ) * ( 3 / 3 ) = 6 / 9 2 / 9 + 2 / 3 = 2 / 9 + 6 / 9 = 8 / 9
*March 11, 2015*

**MATHHHHHHHHHHHHH**

Both answers are correct.
*March 11, 2015*

**Algebra 2**

3 square root( 2 x + 1 ) = 3 square both sides 3 ^ 2 * square root( 2 x + 1 ) ^ 2 = 3 ^ 2 9 * ( 2 x + 1 ) ^ 2 = 9 Divide both sides by 9 2 x + 1 = 1 Subtract 1 to both sides 2 x + 1 - 1 = 1 - 1 2 x = 0 Divide both sides by 2 x = 0
*March 11, 2015*

**Algebra 2**

square root ( 5 - 2 x ) + 5 = 12 Subtract both 5 to both sides square root ( 5 - 2 x ) + 5 - 5 = 12 - 5 square root ( 5 - 2 x ) = 7 Square both sides 5 - 2 x = 49 Subtract 5 to both sides 5 - 2 x - 5 = 49 - 5 - 2 x = 44 Divide both sides by - 2 x = 44 / - 2 x = - 22
*March 11, 2015*

**Algebra 2**

square root ( 2 x - 5 ) = 7 Square both sides 2 x - 5 = 49 Add 5 to both sides 2 x - 5 + 5 = 49 + 5 2 x = 54 Divide both sides by 2 x = 54 / 2 x = 27
*March 11, 2015*

**MATHS**

In google type : Cryptarithmetic Puzzle Solver When you see list of results click on : bach.istc.kobe-u.ac.jp/llp/crypt When page be open in rectangle type: lass+lad=love and click on: Solve Problem have 250 solutions.
*March 6, 2015*

**5th grade math**

2 3/4 = 2 * 4 / 4 + 3 / 4 = 8 / 4 + 3 / 4 = 11 / 4 1 1/2 = 2 * 1 / 2 + 1 / 2 = 2 / 2 + 1 / 2 = 3 / 2 A = L * W = 11 / 4 * 3 / 2 = 33 / 8 = 32 / 8 + 1 / 8 = 4 1/8
*March 5, 2015*

**5th grade math**

1 1/4 = 1 + 1 / 4 = 4 / 4 + 1 / 4 = 5 / 4 5 / 4 * 1 / 5 = 5 / 4 * 5 = 1 / 4
*March 5, 2015*

**Math**

1.) 3 x - 5 y = 2 Add 5y to both sides 3 x - 5 y + 5 y = 2 + 5 y 3 x = 2 + 5 y Subtract 2 to both sides 3 x - 2 = 2 + 5 y - 2 3 x - 2 = 5 y 5 y = 3 x - 2 2 x + 5 y = 13 2 x + 3 x - 2 = 13 5 x - 2 = 13 Add 2 to both sides 5 x - 2 + 2 = 13 + 2 5 x = 15 Divide both sides by 5 5 x...
*March 3, 2015*

**Math**

Substitution method: x – 2 y = 0 Add 2 y to both sides x – 2 y + 2 y = 0 + 2 y x = 2 y 3 x – y ^ 2 = 0 3 * 2 y - y ^ 2 = 0 6 y - y ^ 2 = 0 - y ^ 2 + 6 y = 0 Multiply both sides by - 1 y ^ 2 - 6 y = 0 y * y - 6 y = 0 y * ( y - 6 ) = 0 Obviously solution y = 0 and...
*March 2, 2015*

**Maths**

What mean x 7 y = 5 ? x - 7 y = 5 x + 7 y = 5 x ^ 7 y = 5
*March 2, 2015*

**math**

3.9 / 11.7 = 16.5 / x Multiply both sides by x 3.9 * x / 11.7 = 16.5 * x / x 3.9 x / 11.7 = 16.5 Multiply both sides by 11.7 3.9 x * 11.7 / 11.7 = 16.5 * 11.7 3.9 x = 193.05 Divide both sides by 3.9 3.9 x / 3.9 = 193.05 / 3.9 x = 49.5 ft OR 11.7 = 3.9 * 3 So : 3. 9 / 11.7 = 3....
*March 1, 2015*

**7th grade math**

Correct answer.
*February 27, 2015*

**calculus**

If your expression mean: lim sin ^ 3 ( 3 x ) / ( x sin ( x ^ 2) ) , as x -> 0 then : f ( x ) = sin ^ 3 ( 3 x ) g ( x ) = x sin ( x ^ 2) lim [ f ( x ) / g ( x ) ] as x->0 = lim f ( x ) , as x -> 0 / lim g ( x ) , as x -> 0 = lim sin ^ 3 ( 3 x ) , as x -> 0 / lim ...
*February 27, 2015*

**alg 2**

h = 25 t - 5 t ^ 2 Replace t with 3 h = 25 * 3 - 5 * 3 ^ 2 h = 75 - 5 * 9 h = 75 - 45 = 30 m
*February 24, 2015*

**Math homework**

20 / 8 = 4 * 5 / ( 4 * 2 ) = 5 / 2 = 2.5 min / page 2.5 * 20 = 50 min OR 8 / 20 = 20 / x Multiply both sides by x 8 * x / 20 = 20 * x / x 8 x / 20 = 20 Multiply both sides by 20 8 x * 20 / 20 = 20 * 20 8 x = 400 Divide both sides by 8 8 x / 8 = 400 / 8 x = 50 min
*February 24, 2015*

**maths**

6 / 9 = 8 / x Multiply both sides by x 6 * x / 9 = x * 8 / x 6 x / 9 = 8 Multiply both sides by 9 6 x * 9 / 9 = 8 * 9 6 x = 72 Divide both sides by 6 6 x / 6 = 72 / 6 x = 12 6 : 9 = 8 : 12
*February 24, 2015*

**math**

6 + x = 12 Subtract 6 to both sides 6 + x - 6 = 12 - 6 x = 6
*February 20, 2015*

**ALGEBRA**

x1 = - 1 x2 = 0 x3 = 1 x4 = 2 x2 - x1 = 0 - ( - 1 ) = 0 + 1 = 1 x3 - x2 = 1 - 0 = 1 x4 - x3 = 2 - 1 = 1 y1 = - 2 y2 = 1 y3 = 4 y4 = 7 y2 - y1 = 1 - ( - 2 ) = 1 + 2 = 3 y3 - y2 = 4 - 1 = 3 y4 - y3 = 7 - 4 = 3 Since both x and y increase by a constant difference ( x increases by...
*February 16, 2015*

**math**

m = 5 n = 8 m - n = 5 - 8 = - 3 m - n divided by 4 = - 3 / 4
*February 16, 2015*

**math**

( m - n ) / 4 = ( 5 - 8 ) / 4 = - 3 / 4
*February 16, 2015*

**Pre-Calculus**

2000 = 1990 + 10 M ( t ) = 29.9 ( t + 10 ) ^ 2 + 3892 M ( t ) = 29.9 ( t ^ 2 + 2 t * 10 + 10 ^ 2 ) + 3892 M ( t ) = 29.9 ( t ^ 2 + 20 t + 100 ) + 3892 M ( t ) = 29.9 t ^ 2 + 29.9 * 20 t + 29.9 * 100 + 3892 M ( t ) = 29.9 t ^ 2 + 598 t + 2990 + 3892 M ( t ) = 29.9 t ^ 2 + 598 t...
*February 16, 2015*

**Algebra**

1. C The degree of a monomial is the sum of the exponents of all its variables. 3 + 2 = 5 2. B ( 7 t ^ 2 + 9 ) + ( 6 t ^ 2 + 8 ) = 7 t ^ 2 + 9 + 6 t ^ 2 + 8 = 13 t ^ 2 + 17 3. A 4 D 5. D ( 5 x ^ 3 + 2 ) ( 5 x ^ 3 - 2 ) = 5 x ^ 3 * 5 x ^ 3 + 5 x ^ 3 * 2 - 2 * 5 x ^ 3 - 2 * 2 = ...
*February 12, 2015*

**math**

( 2000 - 40 ) / 200 = 160 / 200 = 40 * 4 / ( 40 * 5 ) = 4 / 5 = 0.8 = 0.8 * 100 % = 80 %
*February 11, 2015*

**science**

1 mile = 1.609344 km When you convert 26.22 miles in kilometers you get: 26.22 * 1.609344 = 42.19699968 km approx. 42.197 km But he marathon is a long-distance running event with an OFFICIAL DISTANCE of 42.195 kilometres. You can type: Marathon in google
*February 9, 2015*

**math,algebra**

A = W * L = 8 * 16 = 128 ft ^ 2
*February 9, 2015*

**math,algebra**

P = Perimeter L = Length W = Width P = 2 W + 2 L = 2 ( W + L ) L = 2 W P = 2 ( W + L ) = 2 ( W + 2 W ) = 2 * 3 W = 6 W 48 = 6 W Divide both sides by 6 48 / 6 = 6 W / 6 8 = W W = 8 ft L = 2 W = 2 * 8 = 16 ft P = 2 ( W + L ) = 2 ( 8 + 16 ) = 2 * 24 = 48 ft
*February 9, 2015*

**Math Question**

B.) Correction. sin ^ 2 x + cos ^ 2 x = 1 and 1 - sin ^ 2 x = cos ^ 2 x But Answer B.)
*February 9, 2015*

**Math Question**

B.) Becouse : sin ^ 2 x + cos ^ 2 x = 1 and sin ^ 2 x - 1 = cos ^ 2 x Other 3 expression are identity.
*February 9, 2015*

**Percentages ques 2**

A = B - 20 % B = B - 0.2 B = 0.8 B A = 0.8 B Divide both sides by 0.8 A / 0. 8 = 0.8 B / 0.8 1.25 A = B B = 1.25 A B = 2 C Divide both sides by 2 B / 2 = C C = B / 2 C = 1.25 A / 2 C = 0.625 A = 0.625 A * 100 /100 = 62.5 % A
*February 9, 2015*

**Percentages**

60 % = 60 / 100 = 0.6 80 % = 80 / 100 = 0.8 x = Number of games in season A team has played so far x - 15 games and won 60 % of the games . So : 0.6 * ( x - 15 ) + 15 = 0.8 x 0.6 x - 0.6 * 15 + 15 = 0.8 x 0.6 x - 9 + 15 = 0.8 x 0.6 x + 6 = 0.8 x Subtract 0.6 x to both sides 0....
*February 9, 2015*

**math**

You want to find two numbers whose product is 10 and whose sum is 18. So solution 1 and solution 2 are same solution. The numbers are: 9 - sqroot ( 71 ) and 9 + sqroot ( 71 )
*February 9, 2015*

**math**

a = first number b = second number Conditions : a * b = 10 a + b = 18 a + b = 18 Subtract a to both sides a + b - a = 18 - a b = 18 - a a * b = 10 a * ( 18 - a ) = 10 18 a - a ^ 2 = 10 - a ^ 2 + 18 a = 10 Multiply both sides by - 1 a ^ 2 - 18 a = - 10 [ Add ( 18 /2 ) ^ 2 = 9...
*February 9, 2015*

**math/algebra**

Copy your question in google. When you see list of results click on : w w w . a l g e b r a . c o m / c g i - b i n / j u m p - t o - q u e s t i o n . m p l You will see solution.
*February 6, 2015*

**Maths**

5 x + y = 35 Subtact 5 x to both sides 5 x + y - 5 x = 35 - 5 x y = 35 - 5 x 3 x - 2 y = 14 3 x - 2 ( 35 - 5 x ) = 14 3 x - 2 * 35 - 2 * ( - 5 x ) = 14 3 x - 70 + 10 x = 14 13 x - 70 = 14 Add 70 to bopth sides 13 x - 70 + 70 = 14 + 70 13 x = 84 Divide both sides by 13 13 x / ...
*February 4, 2015*

**Algebra**

R = Age of Rosa A = Age of Amy Rosa is 14 years older than her sister Amy. R = A + 14 Three years ago, she was three times as old as amy Three years ago, Rosa and Amy was 3 years younger so. R - 3 = 3 ( A - 3 ) Replace R with A + 14 A + 14 - 3 = 3 ( A - 3 ) A + 11 = 3 A - 3 * ...
*February 4, 2015*

**algebra**

3 * 4 + 20 / 4 = 12 + 5 = 17
*February 3, 2015*

**Math**

L = Length = x W = Width = 2 x - 4 x = 2 + 3 t L = x L = 2 + 3 t W = 2 x - 4 = W = 2 ( 2 + 3 t ) - 4 = W = 2 * 2 + 2 * 3 t - 4 = W = 4 + 6 t - 4 = W = 6 t W = 6 t L = 2 + 3 t A = W * L = A = 6 t * ( 2 + 3 t ) = A = 6 t * 2 + 6 t * 3 t = A = 12 t + 18 t ^ 2 t = 2 A = 12 t + 18 ...
*January 30, 2015*

**math**

L = Length of a wire = 24 cm a = The length of square side. P = Perimeter of a square = 4a Length of a wire = Perimeter of a square L = P 24 cm = 4 a Divide both sides by 4 6 cm = a a = 6 cm A = Area of the square = a ^ 2 A = 6 ^ 2 = 36 cm ^ 2
*January 30, 2015*

**Math**

Copy your question in google. When you see list of results click on : w w w . a l g e b r a . c o m You will see answer.
*January 30, 2015*

**algebra**

For quadratic equation : a x ^ 2 + b x + c = 0 The solutions are: x1/2 = [ - b + OR - sqroot ( b ^ 2 - 4 a c ) ] / 2 a Int this case : a = 1 b = 4 c = 6 x1/2 = [ - 4 + OR - sqroot ( 4 ^ 2 - 4 * 1 * 6 ) ] / ( 2 * 1 ) x1/2 = [ - 4 + OR - sqroot ( 16 - 24 ) ] / 2 x1/2 = [ - 4 + ...
*January 30, 2015*

**Algebra**

x = 1.5 f ( 1.5 ) = 3 * 1.5 -2 = 4.5 - 2 = 2.5 Answer : a
*January 27, 2015*

**algebra 1**

n = even number n - 1 = odd number 3 ( n - 1 ) = 4 n - 11 3 n - 3 = 4 n - 11 Subtract 3 n to both sides 3 n - 3 - 3 n = 4 n - 11 - 3 n - 3 = n - 11 Add 11 to both sides - 3 + 11 = n - 11 + 11 8 = n n = 8 = even number n - 1 = 7 = odd number
*January 26, 2015*

**Maths**

Steve, I am from Sarajevo, Bosnia and Herzegovina. English is foreign language for me. Numerator is typing mistake, so what?
*January 26, 2015*

**Maths**

n = numerator d = denominator n = d - 2 ( n - 3 ) / ( d - 3 ) = 3 / 4 ( d - 2 - 3 ) / ( d - 3 ) = 3 / 4 ( d - 5 ) / ( d - 3 ) = 3 / 4 Multiply both sides by 4 4 ( d - 5 ) / ( d - 3 ) = ( 3 / 4 ) *4 4 ( d - 5 ) / ( d - 3 ) = 3 Multiply both sides by ( d - 3 ) 4 ( d - 5 ) ( d - ...
*January 26, 2015*

**Algebra I**

A = 4 B A + B = 160 _____________ A + B = 160 4 B + B = 160 5 B = 160 Divide both sides by 5 B = 160 / 5 = 32 min A = 4 B = 4 * 32 = 128 min
*January 26, 2015*

**algebra**

( 5 x ^ 2 - 7 x + 23 ) + 2 x ^ 2 + 9 x -72 = 5 x ^ 2 + 2 x ^ 2 - 7 x + 9 x + 23 - 72 = 7 x ^ 2 + 2 x - 49
*January 23, 2015*

**math**

- 0.15 ( x - 13 ) ^ 2 + 7.6 = 7 Subtract 7.6 to both sides - 0.15 ( x - 13 ) ^ 2 + 7.6 - 7.6 = 7 - 7.6 - 0.15 ( x - 13 ) ^ 2 = - 0.6 Divide both sides by - 0.15 ( x - 13 ) ^ 2 = - 0.6 / - 0.15 ( x - 13 ) ^ 2 = 4 Take square root to both sides x - 13 = + OR - 2 Add 13 to both ...
*January 23, 2015*

**math**

( - 5 pi / 12 ) rad = - 75 ° cos ( - x ) = cos x cos ( - 5 pi / 12 ) rad = cos ( 75 ° ) 75 ° = 45 ° + 30 ° cos ( A + B ) = cos ( A ) * cos ( B ) - sin ( A ) * Sin ( B ) cos ( 75 ° ) = cos ( 45 ° + 30 ° ) = cos ( 45° ) * cos ( 30 ° ) - ...
*January 22, 2015*

**math**

Remark : a1 = 2 n a2 = 2 ( n + 1 ) a3 = 2 ( n + 2 ) a4 = 2 ( n + 3 ) n is an integer.
*January 22, 2015*

**math**

The even integers are: a1 = 2 n a2 = 2 ( n + 1 ) a3 = 2 ( n + 2 ) a4 = 2 ( n + 3 ) a2 ^ 2 = a1 * a4 [ 2 ( n + 1 ) ] ^ 2 = 2 n * 2 ( n + 3 ) 4 ( n + 1 ) ^ 2 = 4 n * ( n + 3 ) Divide both sides by 4 ( n + 1 ) ^ 2 = n * ( n + 3 ) n ^ 2 + 2 * n * 1 + 1 ^ 2 = n * n + n * 3 n ^ 2 + ...
*January 22, 2015*

**Mathematics**

V = Velocity L = Length t = Time LA = Distance between meeting point and town A LB = Distance between meeting point and town B L = LA + LB = 120 km LA + LB = 120 Subtract LA to both sides LA + LB - LA = 120 - LA LB = 120 - LA VA = Velocity of a car which travelling town A for ...
*January 18, 2015*

**trigometry**

tan theta + cot theta = tan theta + 1 / tan theta = tan theta * tan theta / tan theta + 1 / tan theta = tan ^ 2 theta / tan theta + 1 / tan theta = ( tan ^ 2 theta + 1 ) / tan theta = ( sin ^ 2 theta / cos ^ 2 theta + cos ^ 2 theta ) / tan theta = [ ( sin ^ 2 theta + cos ^ 2 ...
*January 14, 2015*

**algebra**

z ^ - 4 = 1 / z ^ 4 z ^ - 4 / 6 x ^ 2 = ( 1 / z ^ 4 ) / 6 x ^ 2 = 1 / z ^ 4 * 6 x ^ 2 = 1 / [ 6 ( z ^ 4 * x ^ 2 ) = 1 / [ 6 ( z ^ 2 * x ) ^ 2 ]
*January 14, 2015*

**maths**

7 n + 13 = 5 n + 20 Subtract 5 n to both sides 7 n + 13 - 5 n = 5 n + 20 - 5 n 2 n + 13 = 20 Subtract 13 to both sides 2 n + 13 - 13 = 20 - 13 2 n = 7 Divide both sides by 2 n = 7 / 2
*January 12, 2015*

**alegbra 1**

3 x ^ 2 - 4 x + 1 = ( x - 1 ) ( 3 x - 1 ) 3 x ^ 2 - 3 = 3 ( x ^ 2 - 1 ) = 3 ( x + 1 ) ( x - 1 ) ( 3 x ^ 2 - 4 x + 1 ) / ( 3 x ^ 2 - 3 ) = ( x - 1 ) ( 3 x - 1 ) / [ 3 ( x + 1 ) ( x - 1 ) ] = ( 3 x - 1 ) / [ 3 ( x + 1 ) ] = 1 - 4 / [ ( 3 ( x + 1 ) ] Domain : x + 1 # 0 x # - 1 ...
*January 11, 2015*

**math**

1 cm = 1 / 100 m 100,000 x 1 cm = 1000 x 1 / 100 = 1,000 m 1,000 m = 1 km 1 cm on scale = 1 km 7 x 4 cm on scale = 7 km x 4 km = 28 km ^ 2
*January 10, 2015*

**Precal**

H = Height of the lighthouse = 200 ft L = Distance between the lighthouse and a ship theta = The angle of elevation = 21 ° tan theta = H / L tan 21 ° = 200 / L Multiply both sides b L L tan 21 ° = 200 Divide both sides by tan 21 ° L = 200 / tan 21 ° L = 200...
*January 6, 2015*

**college pre-calculus**

Correction : Your equation becomes : ( x + 1) [ x - ( 1 + i ) ] [ x - ( 1 - i ) ] ( x + 1) [ x - ( 1 + i ) ] [ x - ( 1 - i ) ] = ( x + 1 ) ( x ^ 2 - 2 x + 2 ) = x ^ 3 - x ^ 2 + 2 Answer D
*January 6, 2015*

**college pre-calculus**

1) x ^ 3 + a x ^ 2 + b x + c = ( x - x1 ) ( x - x2 ) ( x - x3 ) 2) For an equation with real coefficients, imaginary roots ( if any ) occur in conjugate pairs, i.e. f ( x ) = 0 a polynomial equation with real coefficients an n + i * m an imaginary root of it , then n - i * m ...
*January 6, 2015*

**Math**

2 x / ( x - 1 ) - 9 x / ( x - 2 ) = [ 2 x ( x - 2 ) - 9 x ( x - 1 ) ] / [ ( x - 1 ) ( x - 2 ) ] = [ 2 x * x + 2 x * ( - 2 ) - 9 x * x - 9 x * ( - 1 ) ] / ( x ^ 2 - 3 x + 2 ) = ( 2 x ^ 2 - 4 x - 9 x ^ 2 + 9 x ) / ( x ^ 2 - 3 x + 2 ) = ( - 7 x ^ 2 + 5 x ) / ( x ^ 2 - 3 x + 2...
*January 6, 2015*

**Math**

Your answer is correct.
*January 6, 2015*

**Algebra**

Draw a Cartesian coordinate system. Now : 2 x - y = 4 for x = 0 2 x - y = 4 2 * 0 - y = 4 - y = 4 Multiply both sides by - 1 y = - 4 This is first point ( x = 0 , y = 4 ) for y = 0 2 x - y = 4 2 x - 0 = 4 2 x = 4 Divide both sides by 2 x = 2 This is second point ( x = 2 , y = ...
*January 2, 2015*

**math**

a = first number b = second number Conditions: a + b = 39 2 a + 3 b = 101 ________________ a + b = 39 Subtract b to both sides a + b - b = 39 - b a = 39 - b 2 a = 2 ( 39 - b ) 2 a = 78 - 2 b 2 a + 3 b = 101 78 - 2 b + 3 b = 101 78 + b = 101 Subtract 78 to both sides 78 + b - ...
*January 2, 2015*

**Math**

P = the perimeter = 80 m A = the area W = the width L = the length P = 2 W + 2 L = 2 ( W + L ) 80 = 2 ( W + L ) Divide both sides by 2 40 = W + L Subtract L to both sides 40 - L = W + L - L 40 - L = W W = 40 - L A = W * L A = ( 40 - L ) * L A = 40 L - L ^ 2 A = - L ^ 2 + 40 L ...
*January 2, 2015*

**algebra 1**

5 x - 12 y = - 3 Miltiply both sides by - 2 - 10 x + 24 y = 6 - 10 x + 24 y = 6 + 10 x - 4 y = - 25 __________________ 0 + 20 y = - 19 20 y = - 19 Multiply both sides by 20 y = - 19 / 20 10 x - 24 y = - 6 10 x - 24 * ( - 19 ) / 20 = - 6 10 x - ( 4 * 6 ) * ( - 19 ) / ( 4 * 5...
*December 18, 2014*

**Algebra (Please help!)**

- 1 / 4 / ( 3 / 2 ) = - 1 * 2 / ( 4 * 3 ) = - 2 / 12 = - 2 / ( 2 * 6 ) = - 1 / 6
*December 13, 2014*

**please help (algebra)**

9 / 2 = 18 / 4 3 / 4 - 9 / 2 = 3 / 4 - 18 / 4 = - 15 / 4
*December 10, 2014*

**Math**

3. Becouse : | - x | = x - ( - ( - x ) ) = - x | - x | = - ( - ( - x ) ) mean: x = - x That is true only for x = 0
*December 10, 2014*

**math**

W = L - 4 P = 2 W + 2 L P = 2 ( W + L ) P = 2 ( L - 4 + L ) P = 2 ( 2 L - 4 ) P = 2 * 2 L - 2 * 4 P = 4 L - 8 56 = 4 L - 8 Add 8 to both sides 56 + 8 = 4 L - 8 + 8 64 = 4 L Divide both sides by 4 64 / 4 = 4 L / 4 16 = L L = 16 m W = L - 4 = 16 - 4 = 12 m Proof: P = 2 ( W + L...
*December 9, 2014*

**algebra**

You can write: 4 y - x = - 3 like: - x + 4 y = - 3 Now: - x + 4 y = - 3 + 2 x - 4 y = 14 _________________ - x + 2 x + 4 y - 4 y = - 3 + 14 x + 0 = 11 x = 11 4 y - x = - 3 4 y - 11 = - 3 Add 11 to both sides 4 y - 11 + 11 = - 3 + 11 4 y = 8 Divide both sides by 4 4 y / 4 = 8...
*December 9, 2014*

**Algebra**

If the room have rectangle form then : L = W + 23 P = 2 W + 2 L P = 2 ( W + L ) P = 2 ( W + W + 23 ) P = 2 ( 2 W + 23 ) P = 4 W + 46 290 = 4 W + 46 Subtract 46 to both sides 290 - 46 = 4 W + 46 - 46 244 = 4 W Divide both sides by 4 244 / 4 = 4 W / 4 61 = W W = 61 ft L = W + 23...
*December 9, 2014*

**Calculus**

The solutions of quadratic equation t ^ 2 + 2 t - 1 = 0 are : t = sqroot ( 2 ) - 1 and t = - 1 - sqroot ( 2 ) = - [ 1 +sqroot ( 2 ) ] = - 2.41421 Substitution sin ( x ) = t OR t = sin ( x ) give : sin ( x ) = sqroot ( 2 ) - 1 and sin ( x ) = - 1 - sqroot ( 2 ) = - [ 1 +sqroot...
*December 9, 2014*

**Calculus**

arc sin ( x ) is inverse sine function of x arc sin ( x ) = sin ^ - 1 ( x )
*December 9, 2014*

**Calculus**

sin ^ 2 ( x ) + cos ^ 2 ( x ) = 1 => cos ^ 2 ( x ) = 1 - sin ^ 2 ( x ) y = 2 sin ( x ) - [ 1 - sin ^ 2 ( x ) ] y = 2 sin ( x ) - 1 + sin ^ 2 x y = sin ^ 2 x + 2 sin ( x ) - 1 Substitution sin ( x ) = t y = t ^ 2 + 2 t - 1 x - intercept is a point on the graph where y is ...
*December 9, 2014*

**Algebra**

The vertex of a quadratic equation y = a x ^ 2 + b x + c is either a maximum or a minimum of the function. x = - b / 2 a gives the x - value (or the value of the function) at its vertex. y = f ( - b / 2 a ) gives the y - value (or the value of the function) at its vertex. If ...
*December 2, 2014*

**Calculus**

- 1 / 100 = const. 4 ( pi ) ^ 2 - 9 = const. sin ^ 2 x + cos ^ 2 x = 1 = const. csc x tan x cosx = ( 1 / sin x ) * ( sin x / cos x ) * cos x = 1 = const. The derivative of a constant is zero. Answer : E. All do
*December 1, 2014*

**math**

1 = 6 / 6 3 = 3 * 6 / 6 = 18 / 6 3 5 / 6 = 18 / 6 + 5 / 6 = 23 / 6
*November 24, 2014*

**calculus**

Sorry. v = ds / dt
*November 24, 2014*

**calculus**

a = ds / dt a = ( 1 / 2 ) * [ 1 / sqrt ( 6 t + 3 ) ] * 6 a = 3 / sqrt ( 6 t + 3 ) t = 1 a = 3 / sqrt ( 6 * 1 + 3 ) a = 3 / sqrt ( 6 + 3 ) a = 3 / sqrt ( 9 ) a = 3 / 3 a = 1 m / s ^ 2 Answer a.
*November 24, 2014*

**Algebra 2**

x ^ 2 + 4 y ^ 2 = 16 - x ^ 2 + y ^ 2 = 4 ______________________ 3 y ^ 2 = 12 Divide both sides by 3 y ^ 2 = 12 / 3 = 4 y = + OR - 2 For y = 2 x ^ 2 + 4 y ^ 2 = 16 x ^ 2 + 4 * 2 ^ 2 = 16 x ^ 2 + 4 * 4 = 16 x ^ 2 + 16 = 16 Subtract 16 to both sides x ^ 2 = 0 x = 0 For y = - 2 x...
*November 23, 2014*

**Calculus (PLEASE HELP ASAP!)**

1 ) f" ( x ) = 1 / x ^ 3 = x ^ ( -3 ) f´ ( x ) = integral of x ^ ( -3 ) dx f´ ( x ) = x ^ ( - 3 + 1 ) / ( - 3 + 1 ) + C f´ ( x ) = x ^ ( - 2 ) / ( - 2 ) + C f´ ( x ) = 1 / x ^ 2 / ( - 2 ) + C f´ ( x ) = - 1 / ( 2 x ^ 2 ) + C f´ ( 1 ) = ...
*November 19, 2014*

**math**

1 / 2 kg = 500 g 500 g / 50 g = 10 10 * 7 = 70 nails
*November 15, 2014*

**math**

2 / 5 = 4 / 10 = 0.4 1 / 4 of 0.4 = 0.1 0.4 - 0. 1 = 0.3 = 3 / 10 = 30 / 100 = 30 % OR 1 - 1 / 4 = 3 / 4 ( 2 / 5 ) * ( 3 / 4 ) = 6 / 20 = 2 * 3 / ( 2 * 10 ) = 0.3
*November 15, 2014*

**math**

b = mass of the basket a = mass of the aple b + 12 a = 3105 Subtract 12 a to both sides b + 12 a - 12 a = 3105 - 12 a b = 3105 - 12 a b + 7 a = 1980 3105 - 12 a + 7 a = 1980 3105 - 5 a = 1980 Subtract 1980 to both sides 3105 - 5 a - 1980 = 1980 - 1980 1125 - 5 a = 0 Add 5 a to...
*November 12, 2014*

**algebra**

g = girls age b = boys age g + b = 26 Subtract b to both sides g + b - b = 26 - b g = 26 - b g - 3 = 4 ( b - 3 ) 26 - b - 3 = 4 ( b - 3 ) 23 - b = 4 b - 12 Add b to both sides 23 - b + b = 4 b + b - 12 23 = 5 b - 12 Add 12 to both sides 23 + 12 = 5 b - 12 + 12 35 = 5 b Divide ...
*November 11, 2014*

**math**

By the way : ( 1 - x ) ^ 2 = [ ( - 1 ) ( x - 1 ) ] ^ 2 = ( - 1 ) ^ 2 ( x - 1 ) ^ 2 = 1 * ( x - 1 ) ^ 2 = ( x - 1 ) ^ 2 integral from 0 to 2 - 2 x of ( 2 - 2 x - y ) dy = 2 ( 1 - x ) ^ 2 = 2 ( x - 1 ) ^ 2
*November 4, 2014*

**math**

integral of ( 2 - 2 x - y ) dy = 2 y - 2 x y - y ^ 2 / 2 for y = 0 2 y - 2 x y - y ^ 2 / 2 = 2 * 0 - 2 x * 0 - 0 ^ 2 / 2 = 0 for y = 2 - 2 x 2 ( 2 - 2 x ) - 2 x ( 2 - 2 x ) - ( 2 - 2 x ) ^ 2 / 2 = ( 2 - 2 x ) ( 2 - 2 x ) - ( 2 - 2 x ) ^ 2 / 2 = ( 2 - 2 x ) ^ 2 - ( 2 - 2 x ) ^ ...
*November 4, 2014*

**math**

Substitution rule: y ^ 4 + 1 = t 4 y ^ 3 dy = dt Divide both sides by 4 y ^ 3 dy = dt / 4 integral of y ^ 3 dy / ( y ^ 4 + 1 ) = integral of ( dt / 4 ) / t = ( 1 / 4 ) integral of dt / t = ( 1 / 4 ) ln ( t ) = ( 1 / 4 ) ln ( y ^ 4 + 1 )
*November 4, 2014*

**math**

Replace x with given number. f ( 2 ) = - 3 * 2 + 9 = - 6 + 9 = 3 f ( - 2 ) = - 3 * ( - 2 ) + 9 = 6 + 9 = 15
*October 31, 2014*

**Pre-Calc/Trig...**

( 2 x ^ 3 + x ^ 2 - 5 x + 2 ) / ( x + 2 ) = 2 x ^ 2 - 3 x + 1 2 x ^ 2 - 3 x + 1 = ( x - 1 ) ( 2 x - 1 ) So : 2 x ^ 3 + x ^ 2 - 5 x + 2 = ( x + 2 ) ( x - 1 ) ( 2 x - 1 ) x + 2 is one of fators of : 2 x ^ 3 + x ^ 2 - 5 x + 2
*October 31, 2014*

**Pre-Calc/Trig...**

( 2 x ^ 3+ x ^ 2 - 5 x + 2 ) / ( x + 2 ) = 2 x ^ 2 - 3 x + 1 In google type . calc 101 When you see list of results click on : c a l c 1 0 1 . c o m When page be open click on : long division In rectangle : Divide type : 2x^3+x^2-5x+2 In rectangle : by type : x+2 Then click ...
*October 31, 2014*

**Algebra: PLEASE HELP ME! :(**

Replace x with , b - 2 Firs coordinate is x. In this case : b - 2 Second coordinate is : y = f ( x ) = f ( b - 2 ) So : b - 2 , f( b - 2 )
*October 31, 2014*

**Math**

The dimensions of the box : 51 - 2 x and 45 - 2 x The volume of the box: ( 51 - 2 x ) * ( 45 - 2 x ) * x = 7750 51 * 45 - 2 x * 45 - 2 x * 51 - 2 x * ( - 2 x ) * x = 7750 ( 2295 - 90 x - 102 x + 4 x ^ 2 ) * x = 7750 ( 4 x ^ 2 - 192 x + 2295 ) * x = 7750 4 x ^ 3 - 192 x ^ 2 + ...
*October 30, 2014*

**algebra math**

Formula for a geometric sequence : an = a1 * r ^ ( n - 1 ) an is the nth term, a1 is the first term, r is the common ratio. In this case : a = 8 r = 1 / 2 a1 = 8 * ( 1 / 2 ) ^ ( 1 - 1 ) a1 = 8 * ( 1 / 2 ) ^ 0 a1 = 8 * 1 = 8 a2 = 8 * ( 1 / 2 ) ^ ( 2 - 1 ) a2 = 8 * ( 1 / 2 ) ^ 1...
*October 28, 2014*